Description of oral behavior during the oral processing of heterogeneous apple purees: An application of the temporal check‐all‐that‐apply method. Issue 2 (8th October 2021) - Martin, Christophe; Danten, Virginie; Tournier, Carole
Abstract: The objective of this study was to assess the potential of the temporal check‐all‐that‐apply (TCATA) method to describe oral behavior from the introduction of products into the mouth until swallowing. In particular, we wanted to test the feasibility of the task, the ability to show differences between composite products, and the possibility of segmenting the panel based on the data collected. Terms referring to actions performed during food oral processing (FOP) were used instead of classical sensory descriptors. The evaluation consisted, for a panel of 54 subjects, of checking the boxes corresponding to the actions in progress throughout the consumption of the products. The five products studied were an apple puree and four heterogeneous mixtures that were obtained by adding gel pieces varying in size (two sizes) and firmness (two levels of firmness). The participants did not encounter any particular difficulty in describing in real time the actions in progress during the consumption of the products. Data collected made it possible to describe the sequences of actions carried out during the FOP and to determine the influence of the presence of pieces of gels, their size and their firmness. We highlighted two groups of subjects presenting different behaviors. The subjects in the first one exhibited little difference in processing between the four samples containing the gel pieces, while the subjects in the second group adapted their behavior according to the firmness of the gel pieces. Overall, this exploratory study suggests the ability of TCATA in describing oral behavior during FOP. Future studies should aim at validating it with objective measurements of FOP.